Comparison of 1975, 1998 and 2007 Turkish Earthquake Codes on Selected RC Buildings - Ayache, Mustapha (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Throughout the years Turkey has encountered several disastrous earthquakes that had done major losses in lives and in the economy. The loss was huge and that brought the attention of Ministry of Public Works in Turkey to revise and update their design codes. Turkish Earthquake Codes have been updated and improved to meet the safety levels that are needed for this seismic area. In this thesis, the 1975, 1998, and 2007 Turkish Earthquake Codes are compared. Six different case studies were chosen and designed with different elevations; four case studies containing different type of irregularities while the other two are regular designs. The non-linear static pushover analysis method presented in TEC-2007 was chosen for evaluating and understanding how these buildings behave under a seismic activity. Moreover, the performance, the cost and the damage percentages of the buildings in respect to each of the 1975, 1998, and 2007 Turkish Earthquake Codes were conducted. Subsequently each case was investigated to find out the performance of each code in the event of an earthquake. The study has identified that the 1975 Turkish Earthquake Code is dangerous to follow in seismic activity areas due to most cases not meeting the safety criteria. While on the other hand, the 1998 and 2007 Turkish Earthquake Codes has been identified as safe to follow with minor differences. Keywords: Earthquake, Turkish Earthquake Code, non-linear static pushover, performance, cost, damage percentages.

ÖZ: Türkiye, yıllar içerisinde ekonomisine ağır zararlar veren ve büyük can kayıplarının yaşandığı depremlerle karşı karşıya kalmıştır. Kayıplar çok büyüktü ve bu Bayındırlık Bakanlığı’nın ilgisini, tasarım kodlarını gözden geçirip düzenlemeye yöneltti. Türk Deprem Yönetmelikleri güncellendi ve bu sismik bölgenin güvenlik ihtiyaçlarını karşılamak üzere geliştirildi. Bu çalışmada, 1975, 1998 ve 2007 Türk Deprem Yönetmelikleri karşılaştırılmıştır. Altı farklı vaka incelemesi seçildi ve farklı yüksekliklerde tasarlandı; dört vaka incelemesi birbirinden farklı düzensizlikler içerirken diğer iki vaka incelemesi düzensizlik içermiyordu. TEC-2007’de sunulan statik itme analiz metodu binaların sismik aktivite karşısında nasıl tepki verdiğini ölçmek ve davranışını anlamak için seçilmiştir. Ayrıca, bu binaların performans seviyeleri, maliyet ve hasar yüzdeleri 1975, 1998 ve 2007 Türk Deprem Yönetmeliklerine göre hesaplanıp karşılaştırılmıştır. Bu çalışmada seçilen, 1975 Türk Deprem Yönetmeliği ile tasarlanan çoğu binanın elde edilen yapısal performans seviyesine bağlı olarak güvenli olmadığı görülmüştür. Diğer yandan, 1998 ve 2007 Türk Deprem Yönetmeliklerine göre tasarlanmış vakaların güvenli olduğu saptanmıştır. Anahtar Kelimeler: Deprem, Türk Deprem Yönetmeliği, statik itme analizi, performans, maliyet, hasar yüzdeleri.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2017. Supervisor: Assist. Prof. Dr. Giray Özay.
Keywords: Civil Engineering; Earthquake resistant design; Buildings--Earthquake effects; Earthquake; Turkish Earthquake Code; non-linear static pushover; performance; cost; damage percentages